2015
DOI: 10.4028/www.scientific.net/amr.1091.19
|View full text |Cite
|
Sign up to set email alerts
|

Crystallite Cluster Structure Formation Resulting from Semi-Enclosed Cage Interaction in TSI-POSS/PU Hybrid Composites

Abstract: Trisilanolisobutyl polyhedral oligomeric silsesquioxane (TSI-POSS) with three hydroxyl functional groups pendent to a semi-enclosed cage, was incorporated in concentrations of 7, 13 and 22 wt% into 4,4'-methylenebis (phenyl isocyanate) (MDI) and glycerol propoxylate to prepare TSI-POSS/PU hybrid composites as a heavy linking node in backbone, respectively. The domain micro-structures of these composites were investigated by FTIR, wide angle X-ray scattering (WAXS) and molecular dynamics simulation approach. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 11 publications
(9 reference statements)
0
1
0
Order By: Relevance
“…Using trisilanol isobutyl POSS and TDI under the catalysis of dibutyltin dilaurate (DBTDL), Oaten 73 and Pan et al 74,75 obtained a transparent POSS/PU film with a lamellar network structure shown in Figure 15. The interactions of strong hydrogen bonds in the amide groups of urethanes and the interactions of long-range hydrophobicity between the hexamethylene groups and isobutyl groups led to the long range ordered lamellar structure of the hybrid.…”
Section: Hydroxy-possmentioning
confidence: 99%
“…Using trisilanol isobutyl POSS and TDI under the catalysis of dibutyltin dilaurate (DBTDL), Oaten 73 and Pan et al 74,75 obtained a transparent POSS/PU film with a lamellar network structure shown in Figure 15. The interactions of strong hydrogen bonds in the amide groups of urethanes and the interactions of long-range hydrophobicity between the hexamethylene groups and isobutyl groups led to the long range ordered lamellar structure of the hybrid.…”
Section: Hydroxy-possmentioning
confidence: 99%